TARI BUAI-BUAI DI KANAGARIAN PAUH IX KECAMATAN KURANJI KOTA PADANG: TINJAUAN KOREOGRAFI - Riana Nasmi; Darmawati Darmawati; Desfiarni Desfiarni (SENDRATASIK UNP, 2018)
Abstract This article aims to disclose and describe about "review Choreography Dance Delight-Delight in Kanagarian Pauh IX Subdistrict Kuranji Padang city". This qualitative research study with the method descriptive analysis. The object examined was the dance of Delight-Delight in Kanagarian Pauh IX Subdistrict Kuranji Padang city. Research instrument is the researcher himself, and assisted with the instruments supporting such as stationery, photo cameras, cassette cd and pendrive. The type of data in this study is the primary data and secondary data. Engineering data collection done by the study of librarianship, observation/observation, interviews. The concept is used to analyze data are data collection, data reduction, withdrawal and presentation of conclusions. The results showed that views on choreography dance Delight-Delight consists of form and content. The form includes: dancer (4 person female dancer), motion farmed (maknawi motion) 14 motif, top design (design 8 above), the design of the floor (horizontal, rectangular), dramatic design (single cone), the composition of the groups of 4 people (large group), music (dance accompaniment vocals dendang, talempong, bansi and gandang), costumes (male costumes), the properties of the oil bottles (dama). The content includes: the idea of dance Delight-Delight comes from a family that worked in the rice fields of the mother membuaikan her crying and dad sing dendang. The atmosphere of dance Delight-Delight, namely: the quiet atmosphere, passion and joy.Keywords: dance Delight-Delight